From Model to Model. The narrative between drawing and digital reproduction of Donatello’s Pulpit - Parrinello, Sandro; Picchio, Francesca; La Placa, Silvia (Od modelu do modelu. Narracja między rysunkiem a cyfrową reprodukcją ambony Donatella, 2022)
The paper aims to consider the narrative and interpretative contribution that digital models can make to heritage archiving date and enhancement, through an investigation conducted on Donatello’s Pulpit in Prato. The pulpit is an architectural work of sophisticated decoration and constitutes a stage in the Ostension of the Sacra Cintola ceremony. The relic of the belt that encircled the clothes of the Virgin is preserved in the Cathedral of Santo Stefano. On the main façade of the church a copy of Donatello’s work is placed. The original opera is kept in the Museum of the same Cathedral. Today, the modalities of communication and transmission of cultural heritage acquire new features with the use and implemention of digital technology. Reality-based 3D models become increasingly accurate digital copies that duplicate the space and character of architectural works, constituting not only copies but serving as critical reinterpretations that express a formal synthesis of object complexity. The documentation activities carried out have made it possible to generate three-dimensional databases of the two pulpits, the original one and the copy. From digital databases 3D models and printed models have been developed to dialogue in the museum exhibition with the Renaissance opera and its history.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 71-82
Keywords: architektura; 3D survey; digital twin; 3D printing; Donatello's Pulpit; badanie 3D; cyfrowa kopia; druk 3D; ambona Donatella